Proliferin-1 Ameliorates Cardiotoxin-Related Skeletal Muscle Repair in Mice. (20th November 2021) - Goto, Hiroki; Inoue, Aiko; Piao, Limei; Hu, Lina; Huang, Zhe; Meng, Xiangkun; Suzuki, Yusuke; Umegaki, Hiroyuki; Kuzuya, Masafumi; Cheng, Xian Wu
Abstract : Background . We recently demonstrated that proliferin-1 (PLF-1) functions as an apoptotic cell-derived growth factor and plays an important role in vascular pathobiology. We therefore investigated its role in muscle regeneration in response to cardiotoxin injury. Methods and Results . To determine the effects of PLF-1 on muscle regeneration, we used a CTX-induced skeletal muscle injury model in 9-week-old male mice that were administered with the recombinant PLF-1 (rPLF-1) or neutralizing PLF-1 antibody. The injured muscles exhibited increased levels of PLF-1 gene expression in a time-dependent manner. On day 14 after injury, rPLF-1 supplementation ameliorated CTX-induced alterations in muscle fiber size, interstitial fibrosis, muscle regeneration capacity, and muscle performance. On day 3 postinjury, rPLF-1 increased the levels of proteins or genes for p-Akt, p-mTOR, p-GSK3 α / β, p-Erk1/2, p-p38MAPK, interleukin-10, Pax7, MyoD, and Cyclin B1, and it increased the numbers of CD34 + /integrin- α 7 + muscle stem cells and proliferating cells in the muscles and/or bone marrow of CTX mice. An enzyme-linked immunosorbent assay revealed that rPLF-1 suppressed the levels of plasma tumor necrosis factor- α and interleukin-1 β in CTX mice. PLF-1 blocking accelerated CTX-related muscle damage and dysfunction. In C2C12 myoblasts, rPLF-1 increased the levels of proteins for p-Akt, p-mTOR, p-GSK3 α / β, p-Erk1/2, and p-p38MAPK as well as cellular functions; and these effects were diminished by the depletion of PLF-1 or silencing of its mannose-6-phosphate receptor. Conclusions . These findings demonstrated that PLF-1 can improve skeletal muscle repair in response to injury, possibly via the modulation of inflammation and proliferation and regeneration, suggesting a novel therapeutic strategy for the management of skeletal muscle diseases.